Functional Generating Bite Therapy in Children During Growth and Development Period - Harun Achmad; Nurhayani Safitri; Yana Paromova; Vitaly V. Goncharov; Risti Saptarini Primarti; Eriska Riyanti (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Function generating bite is an individualized functional appliance made from acrylic resincomprised of several components namely: SS bite blocks, buccal shields, expansion coil and palatal button.This appliance enables teeth reposition entirely based on the temoporomandibular joint physiologicalcondition and avoiding cups-to-cusp misalignment. This is due to the fact that the SS bite block allows opencontact in the posterior region to open the mandible and regulate/reposition the mandible in three differentplanes during orthodontic movement. One of the vital mechanisms of bite block is occlusal plane levelingand dental arch parallelism to prevent the occurrence of dental trauma. Method: In this systematic review,article search was performed using Google Search and Pubmed. Articles published from 2000 and 2020were included. Seven articles were found which include: 7 articles from electronic search and 0 articles frommanual search, 7 articles were screened, 1 article was excluded and 6 articles were included for feasibilitytest and 6 complete articles were included. Results: There were 6 articles on functional generating bite thatcan correct malocclusion whilst increasing the masticatory function. Conclusion: Function generating biteis not only able to correct malocclusion but can also have an effect on mastication, hence this appliance canbe used as a therapeutic tool for masticatory function in children during growth and development.